Women's centrality of life domains: the Israeli case. Issue 4 (27th January 2022) - Kay, Avi; Sharabi, Moshe
Abstract : Purpose: This article aims to provide an examination of the impact of Jewish religious tradition on attitudes toward life domains among Jewish Israeli women. This is the first study of importance of life-domains among women in the ultra-Orthodox community: the fastest growing population in Israel. This population exhibits a unique occupational pattern in which women are the primary economic actors. As women are transitioning into more central occupational and economic players throughout the world, this research has both theoretical and practical implications. Design/methodology/approach: In total, 567 employed Jewish Israeli women (309 secular, 138 traditional and 120 ultra-Orthodox) completed a survey about relative importance of life domains. Responses were analyzed via mean-comparison tests, ANOVA and regression analysis. Findings: Surprisingly, religiosity was associated with higher lower work centrality. Work centrality was the highest among ultra-Orthodox women, and family centrality the lowest. Centrality of religion increased and centrality of leisure decreased with religiosity. No differences emerged regarding centrality of community. Research limitations/implications: A limitation of this study is that attitudes toward life domains are based on one-time responses to one question. With that, the psychometric characteristics of the measure and its wide-spread use indicate its acceptability and applicability for the issue studied. Practical implications: The data point to changes in the attitudes of ultra-Orthodox women toward life-domains. Those changes and the increased presence of these women at the workplace challenge both organizational and community leaders to reexamine how to best react to and benefit from the above. Social implications: Ultra-orthodox society is a fundamentalist, enclave society that has, generally, been able to retain traditional internal social and familial patterns until now. However, increased exposure of community members – and particularly women – to a variety of organizations and individuals operating in them, may be contributing to changes in attitudes of those women regarding their traditional social and familial roles. Originality/value: This study closes gaps in research examining the impact of religion and of gender on work attitudes. It does so among women in the fastest growing population of Israel, that exhibit a unique occupational pattern that can contribute to both theoreticians and policy planners regarding implications of the transition of women to more central economic roles.